Criminal law aspects of piracy at sea according to the UNCLOS with reference to the Croatian legal system - Buhovac, Maja (Array, 2020)
Piracy is traditionally one of the oldest forms of violation of international law and a global threat to maritime traffic. It is a serious international offense against which criminal protection is ensured in the domestic legal system, relying on the postulates of international maritime law, and in particular the Convention on the Law of the Sea. In this paper, the authors deal with the legal analysis of the incrimination of piracy at the international and national levels. In relation to the Republic of Croatia, the authors present recent regulations regarding this international criminal offense in the domestic legal system. This paper aims to point out the fundamental problems caused by the existing regulations regarding this international crime, especially when it comes to jurisdiction over piracy, universal jurisdiction, taking over criminal prosecution, etc.